Clinical practice outcomes and differential results in maternal and neonatal morbidity among pregnant women in Spain who are candidates for a normal birth: a cross-sectional study - Paula Parás-Bravo; Ana Casteleiro; M Santibanez; Amada Pellico-Lopez; María Paz-Zulueta (BMJ Open)
Objective To determine the percentage of pregnant women who are potential candidates for a normal birth in the region of Cantabria, Spain. Also, to compare the main clinical practice outcome indicators and the rates of maternal and neonatal morbidity among the group of candidate women versus non-candidates.Design A cross-sectional study.Setting A tertiary Hospital in Cantabria (Northern region of Spain).Participants The study population comprised the total number of hospital births that took place between 1 January 2014 and 31 December 2014 (n=3315).Results Secondary registers were accessed to review the main indicators of care and the outcome of births. The χ2 test or the Student’s t-test were used to compare both groups for the categorical and continuous variables, respectively. In total, 1863 births (56.20%) were candidates for applying the strategy of care for a normal birth. In 50.86% of these candidate births, an episiotomy was performed, compared with 60.96% in the group of non-candidates (p<0.001). Regarding caesarean sections, these were carried out in 19.32% of the candidate births, compared with 26.79% of non-candidate births (p<0.001). Furthermore, there were statistically significant differences between the groups according to the type of birth, the need for instrumental birthing methods, the existence of perineal tears, Apgar scores and the requirement for the infant to be admitted to the neonatal intensive care unit.Conclusions Our results suggest a differential clinical practice, in line with the recommendations of the Clinical Practice Guidelines for Care of Normal Birth. Nonetheless, improvements are necessary regarding the care provided to women and infants, as the percentages of episiotomies and caesarean sections are still high when compared with current standards and compared with other reports.